Implementation of Finite State Automata Method in Text to Speech Conversion System - Meiyanti, Rini; Sandy, Cut Lika Mestika (Journal of Advanced Computer Knowledge and Algorithms, 2024)
Sound processing uses a variety of methods. One of them is converting writing into sound or commonly known as Text To Speech.Text To Speech is a tool for converting writing input into sound by changing the phoneme of writing.Text To Speech Text To Speech consists of two sub-systems namely word to phoneme converters and phoneme to speech converter. The phoneme itself consists of word fragments that have different speech from one another with each other. To perform the phoneme separation process, the Finite State Automata method. Finite State Automata can recognise the simplest language and is an abstract machine whose input and output are discrete. The input system that is processed by the system only consists of two words. If there are more than two word inputs, the programme will not be able to perform word separation properly. After the word separation is done, then the system performs phoneme to speech converter.The resulting speech is processed by the Indo_TTS database which was database developed using the diphone prosody method concatenation prosody methodThe word that has been separated will be stored into the MySQL database as a result of words that have been tested by the system. Later this system will be intended for general public, students and people with speech impairment. The percentage of successful syllable separation and homograph sound output is 98.7% in the programme's success rate.